2012
DOI: 10.1371/journal.pntd.0001834
|View full text |Cite
|
Sign up to set email alerts
|

Partially Neutralizing Potency against Emerging Genotype I Virus among Children Received Formalin-Inactivated Japanese Encephalitis Virus Vaccine

Abstract: BackgroundGenotype I (GI) Japanese encephalitis virus (JEV) that replaced GIII virus has become the dominant circulating virus in Asia. Currently, all registered live and inactivated JEV vaccines are derived from genotype III viruses. In Taiwan, the compulsory JEV vaccination policy recommends that children receives four doses of formalin-inactivated Nakayama (GIII) JEV vaccine.Methodology/Principal FindingsTo evaluate the influence of genotype replacement on the post-vaccination viral neutralizing ability by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 45 publications
6
49
1
Order By: Relevance
“…It is now very probably the most widespread genotype in Asia, which was otherwise found to be lethal for humans [9], [29][33]. However, to date, vaccines are only derived from genotype III strains; whereas protective levels of cross-reactive neutralizing antibodies of these vaccines were found against the various circulating genotypes, variations between genotypes call for further studies [34], [35]. In particular, since the immune response against genotype I was less pronounced, its duration should be addressed [34].…”
Section: Jev Spatial Epidemiologymentioning
confidence: 99%
“…It is now very probably the most widespread genotype in Asia, which was otherwise found to be lethal for humans [9], [29][33]. However, to date, vaccines are only derived from genotype III strains; whereas protective levels of cross-reactive neutralizing antibodies of these vaccines were found against the various circulating genotypes, variations between genotypes call for further studies [34], [35]. In particular, since the immune response against genotype I was less pronounced, its duration should be addressed [34].…”
Section: Jev Spatial Epidemiologymentioning
confidence: 99%
“…15,20,21 It has been found that antibodies elicited by JE-VAX (Nakayama strain) among Taiwanese children show reduced neutralizing potency against the genotype of the emerging GI JEV strain. 22 Taiwan has been using an inactivated mouse brain Nakayama-NIH vaccine strain since 1968, except for the brief use of an inactivated freeze-dried Beijing vaccine strain in 1988. It has been reported that the JE-VAX had several disadvantages, including vaccine-induced adverse events and the need for two or three primary doses plus boosters.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama vs. Beijing-1 or SA14-14-2, or any of these vs. other wild-type G-III strains) with MBDI, SA14-14-2 LAV, JE-CV as well as Vero CCDI vaccines, although the differences in SCRs or GMTs are not significant statistically. 22,24,25,27,31,65,70,71,117,120,122,136,[165][166][167] This differential neutralization as well as protection against G-III viruses has also been shown in mouse challenge studies. 168 Other studies have shown no such differences or higher GMTs with the heterologous virus strains.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 97%
“…In general, these studies have shown that NAb titres are highest against G-II and homologous G-III viruses, followed by G-IV and heterologous G-III viruses, whereas titres against G-I viruses are the lowest, and in some cases below protective levels. 22,[24][25][26][27][28][29] A recent study specifically evaluated the ability of a G-III virus to elicit protective responses in mice, and the ability of human post-vaccinal and acute phase sera to neutralize G-V viruses. The study found that (a) NAb titres in mice immunized with either G-III or G-V virus were higher with homologous viruses but poor against G-V, (b) the SA14-14-2 LAV or the P-3 inactivated vaccines were less protective against G-V virus challenge in mice, and (c) both GMTs and SPRs were poor against G-V virus, intermediate against G-I virus, and highest against G-III virus with both post-vaccinal and acute phase human sera.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 99%
See 1 more Smart Citation